2018
DOI: 10.1165/rcmb.2017-0410oc
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Cytokine Profiles during Pregnancy Predict Asthma in Children of Mothers without Asthma

Abstract: Little is known about whether maternal immune status during pregnancy influences asthma development in the child. We measured cytokine production in supernatants from mitogen-stimulated peripheral blood immune cells collected during and after pregnancy from the mothers of children enrolled in the Tucson Infant Immune Study, a nonselected birth cohort. Physician-diagnosed active asthma in children through age 9 and a history of asthma in their mothers were assessed through questionnaires. Maternal production of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 48 publications
2
22
0
2
Order By: Relevance
“…An allergic reaction triggers the imbalance of immune responses, including mast cells, eosinophils, neutrophils, and lymphocytes. During pregnancy, the maternal ratios of IFN-γ/IL-13 and IFN-γ/IL-4 are associated with a lower prevalence of childhood asthma ( 28 ). In a previous study, the increased prevalence of allergic rhinitis/conjunctivitis/asthma is associated with various IMIDs, including SLE, Sjögren's syndrome, myasthenia, vitiligo, and psoriasis ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…An allergic reaction triggers the imbalance of immune responses, including mast cells, eosinophils, neutrophils, and lymphocytes. During pregnancy, the maternal ratios of IFN-γ/IL-13 and IFN-γ/IL-4 are associated with a lower prevalence of childhood asthma ( 28 ). In a previous study, the increased prevalence of allergic rhinitis/conjunctivitis/asthma is associated with various IMIDs, including SLE, Sjögren's syndrome, myasthenia, vitiligo, and psoriasis ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies looking at maternal stress during pregnancy and maternal obesity have also shown similar findings, with differences in DNA methylation depending on the mother's status (54). A study investigating maternal immune status during pregnancy found that while maternal production of IL-13, IL-4, IL-5, IFN-γ, IL-10, and IL-17 during pregnancy was unrelated to childhood asthma, the ratios of IFN-γ/IL-13 and IFN-γ/IL-4 during pregnancy were associated with a decreased risk of asthma (58). In utero and early exposures to farm and animal barns is protective against asthma even in genetically similar Amish and Hutterite populations (59).…”
Section: Maternal Factors Epigenetics the Microbiome And Asthmamentioning
confidence: 99%
“…Interestingly, this relationship was found for pre-natal but not post-natal maternal cytokine levels, was evident in children of non-asthmatic but not asthmatic mothers, and held for maternal but not paternal cytokines. Moreover, this relationship was independent of childhood allergy (13).…”
Section: Going One Step Backwards: Maternal Influences On Childhood Amentioning
confidence: 94%